FORMULASI DAN EVALUASI NANO HIDROGEL EKSTRAK DAUN SERUNAI (Chromolaena odorata L.) DENGAN VARIASI KONSENTRASI POLIMER CARBOPOL 980 - Syafira Nabillah; Noval Noval; Nur Hidayah (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2022)
Hydrogel is an ideal preparation as a wound dressing because it can provide a cold sensation that can reduce swelling in the wound area. Nanoparticles are particles that have a size of 1-1000 nm. Nanoparticles have the advantage of reducing the particle size and delivering the active substance to the target site. In the manufacture of nanohydrogels it is necessary to have a gelling agent in order to obtain a preparation that meets the requirements. In this study, nanohydrogels were made using Chrysanthemum leaf extract (Chromolaena odorata L.) as the active substance and made with various concentrations of carbopol 980 as a gelling agent. The purpose of this study was to determine the effect of variations in the concentration of carbopol 980 on nanohydrogel preparations of chrysanthemum leaf extract. The method used is Quasi Experimental Design. Simplicia was made into extracts and then made into nano preparations and evaluated. Data were analyzed using One Way Anova and Kruskal-Wallis. The particle size of Formula I nanohydrogel preparation was obtained at 412.9 nm. The results of the evaluation of the preparation showed that the nanohydrogel of chrysanthemum leaf extract with variations in the concentration of carbopol 980 had no effect on homogeneity, but it did affect the pH, viscosity, dispersibility, and adhesion test as shown in the One Way Anova statistical test (p<0.05). From the evaluation results, the ideal formula for nano hydrogel preparations was found in formula I with a carbopol 980 concentration of 0.5%.